2021
DOI: 10.1002/er.7536
|View full text |Cite
|
Sign up to set email alerts
|

High‐performance Te‐doped Co 3 O 4 nanocatalysts for oxygen evolution reaction

Abstract: To reduce the overpotential of electrocatalytic oxygen evolution reaction (OER) for high-efficiency water splitting, a series of 2 to 5 nm ultrafine spinel Co 3 O 4 nanoparticles (NPs) with varied amount of lattice-doped Te (XTe-Co 3 O 4 , X represents the nominal molar ratio Te/Co of 0, 2, 4, 6, 8%) as catalysts were prepared through a simple hydrothermal synthesis method. The 6% Te-Co 3 O 4 catalyst was optimized to obtain the overpotential as low as 313 mV at 10 mA cm À2 , a small Tafel slope of 75 mV dec À… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…The peaks in SLCOCl 0.15 exhibit a deviation to a higher wavenumber, which can be attributed to the limiting effect of photons caused by the increase in atomic vacancy defects in the lattice. 47 These results together confirmed that the introduction of Cl significantly increases the composition of oxygen defects, which is beneficial to the improvement of OER performance.…”
Section: ■ Results and Discussionsupporting
confidence: 54%
“…The peaks in SLCOCl 0.15 exhibit a deviation to a higher wavenumber, which can be attributed to the limiting effect of photons caused by the increase in atomic vacancy defects in the lattice. 47 These results together confirmed that the introduction of Cl significantly increases the composition of oxygen defects, which is beneficial to the improvement of OER performance.…”
Section: ■ Results and Discussionsupporting
confidence: 54%
“…43 Meanwhile, the bands at 277, 371 and 657 cm −1 correspond to the stretching vibration of Co 3 O 4 . 44,45 The Raman results showed that CuMoO 4 @Co 3 O 4 was successfully synthesized on the surface of the electrode.…”
Section: Resultsmentioning
confidence: 98%
“…As explained, the nanoparticles clump together and form massive particles. The aggregation of nanoparticles has been described as an indication of metallic nanoparticle production processes [ 55 , 56 ].…”
Section: Resultsmentioning
confidence: 99%